Risk Factors Affecting Complications in Patients with Gallbladder Inflammation Due to Gallstones Following Initial Antibiotic Treatment - Kritnikornkul, Amornchai; Vanichkajorn, Paradorn (The Thai Journal of Surgery, 2025)
Background: In 2019, the COVID-19 pandemic limited the timing of surgery in patients with acute calculous cholecystitis (AC), resulting in delayed laparoscopic cholecystectomy (LC) operations for more than three months, according to the FSSA Clinical guide to surgical prioritization during the Coronavirus pandemic, 2022. Objective: This study aimed to determine the risk factors for gallstone-related complications within 90 days after acute calculous cholecystitis (AC). Materials and Methods: From June 2019 to June 2021, retrospective medical records were reviewed from a single center, tertiary care hospital. A total of 184 patients who were older than 18 years, admitted with AC grade I-Il according to Tokyo guidelines 2018, and treated with conservative therapy were included. Patients with severe cholecystitis, cholangitis, or choledocholithiasis were excluded. Data including age, sex, comorbidities, laboratory results, and imaging findings were collected. Multivariable binary regression was performed to identify the risk factors for gallstone-related complications and presented with a risk ratio (RR) and 95% confidence interval (CI). Gallstones-related complications such as recurrent cholecystitis, cholangitis, choledocholithiasis, and pancreatitis were recorded. Results: Among the 184 patients, thirty-two (17.4%) experienced gallstone-related complications within 90 days after receiving conservation treatment for AC. The risk factors determined were white blood cell counts (WBC) ≥ 12000 cells/mL (Adj. RR 2.6), Gallbladder wall thickness ≥ 10 mm (Adj. RR 3.0), and Serum bicarbonate (HCO3) < 22 mmol/L (Adj.RR 0.4). The model can predict gallstone-related complications for 67%. Conclusion: In the upcoming events of the next pandemic, AC patients with WBC ≥ 12,000 cells/mL, gallbladder wall thickness ≥ 10 mm, and HC03 < 22 mmol/L should be selected as a priority for early LC over regular AC patients to reduce gallstone-related complications.